Application of Double Loop Problem Solving to Improve Mathematical Literacy Skills in Junior High School Students in Learning to Build a Flat Side Space - Permata, Intan; Panglipur, Indah Rahayu; Hidayatin, Nur (Journal of Education and Learning Mathematics Research (JELMaR), 2024)
The implementation of learning that tends to be monotonous without paying attention to the active participation of students is one factor contributing to the low mathematical literacy students' skills. The purpose of the study is to explain how to improve mathematical literacy after using the double-loop problem-solving method in learning to build a flat side space. The type of research conducted uses qualitative descriptive with a case study approach. This research was conducted at SMPN 2 Bangsalsari on grade VIII students totaling 8 boys and 7 girls. The data collection technique uses tests, interviews, and observations Interview sheets. observation sheets, and test questions with descriptions are used in the data collection tool. According to the study's findings, both teacher and student activities increased during the course of the study. This is consistent with an increase in the average score for mathematical literacy skills following the introduction of double-loop problem-solving learning. Thus, it very well may be presumed that the use of the twofold circle critical thinking learning model can further develop the numerical proficiency capacity of middle school understudies.